Citizen Engagement Activities: Applying Behaviour Change Techniques in Sustainable Clothing Consumption - Lewe, Elina; de Lamballerie, Edith (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The study explores the application of Behaviour Change Techniques (BCTs) in promoting sustainable clothing consumption. The fashion industry significantly impacts the environment, and despite consumer interest in sustainable options, adoption remains low, and a green gap persists. This research aims to identify effective methods to encourage sustainable behaviours. BCTs, a theoretical framework originally used in health contexts, are applied here to sustainable clothing consumption. Four citizen engagement activities were conducted, each incorporating different BCTs. Surveys were conducted before and after the activities to measure their effectiveness. The study found that certain BCTs (providing information on social and environmental consequences, education, and instructions on how to perform behaviours), significantly correlated with participants’ intentions to adopt sustainable clothing consumption behaviours. These findings suggest that interventions combining impact awareness through information with action are most effective. The study highlights the potential of BCTs to guide and evaluate interventions aimed at reducing the green gap in sustainable clothing consumption.